A self-powered closed-loop brain-machine-interface system for real-time detecting and rapidly adjusting blood glucose concentration. (March 2022) - Yang, Guangyou; Tang, Yong; Lin, Tao; Zhong, Tianyan; Fan, Yaowei; Zhang, Yan; Xing, Lili; Xue, Xinyu; Zhan, Yang
Abstract: The traditional methods of detecting and adjusting blood glucose concentration, such as blood analysis and insulin injection, may delay the treatment of metabolic disease. Here, a new self-powered closed-loop brain-machine-interface system for real-time detecting and rapidly adjusting blood glucose concentration has been fabricated. The system can work without external power supply and be self-powered by the body motion itself, which can meet the requirement of immediate treatment. The system mainly consists of active blood glucose sensor, energy harvester, micro-control unit and brain stimulator. The blood glucose sensor made of enzyme/ZnO nanowire arrays can output piezoelectric voltage under the driving of body motion, and the output can be treated as the glucose-detecting signal through the biosensing-piezoelectric coupling effect. A piezoelectric ceramic device as the energy harvester can convert the body mechanical energy into electricity for powering the whole system. The micro-control unit outputs brain stimulation pulse to the dorsomedial part of the ventromedial hypothalamus (VMHdm) in the brain upon abnormal blood glucose concentration. In mouse samples, the brain stimulator connected to the VMHdm augments the expression of regulatory nerve receptors to achieve rapid increase of blood glucose concentration (39% within 10 min). Thus, a closed loop is formed among the body, brain and system. This self-powered closed-loop approach improves the accessibility of physiological insights and extends brain-machine-interface application in precision medicine for metabolic diseases. Graphical Abstract: A self-powered closed-loop brain-machine-interface system for real-time detecting and rapidly adjusting blood glucose concentration has been realized. The blood glucose sensor made of enzyme/ZnO nanowire arrays can output piezoelectric voltage under the driving of body motion, and the output can be treated as the glucose-detecting signal through the biosensing-piezoelectric coupling effect. The micro-control unit outputs brain stimulation pulse to the dorsomedial part of the ventromedial hypothalamus (VMHdm) in the brain, and in mouse samples, we achieve rapid increase of blood glucose concentration (an average increase of 39% within 10 min). ga1 Highlights: A novel closed-loop system for rapidly adjusting the blood glucose concentration. The self-powered blood glucose sensor can be driven by the body itself. These blood glucose sensing signals can be converted into brain stimulation signals. The brain-computer interface system successfully adjusts the blood glucose concentration of mice.